The impact of viraemia on inflammatory biomarkers and CD4+ cell subpopulations in HIV-infected children in sub-Saharan Africa. (1st August 2021) - Prendergast, Andrew J.; Szubert, Alexander J.; Pimundu, Godfrey; Berejena, Chipo; Pala, Pietro; Shonhai, Annie; Hunter, Patricia; Arrigoni, Francesca I.F.; Musiime, Victor; Bwakura-Dangarembizi, Mutsa; Musoke, Philippa; Poulsom, Hannah; et al.
Abstract : Objective: To determine the impact of virological control on inflammation and cluster of differentiation 4 depletion among HIV-infected children initiating antiretroviral therapy (ART) in sub-Saharan Africa. Design: Longitudinal cohort study. Methods: In a sub-study of the ARROW trial (ISRCTN24791884), we measured longitudinal HIV viral loads, inflammatory biomarkers (C-reactive protein, tumour necrosis factor alpha, interleukin 6 (IL-6), soluble CD14) and (Uganda only) whole blood immunophenotype by flow cytometry in 311 Zimbabwean and Ugandan children followed for median 3.5 years on first-line ART. We classified each viral load measurement as consistent suppression, blip/post-blip, persistent low-level viral load or rebound. We used multi-level models to estimate rates of increase or decrease in laboratory markers, and Poisson regression to estimate the incidence of clinical events. Results: Overall, 42% children experienced viral blips, but these had no significant impact on immune reconstitution or inflammation. Persistent detectable viraemia occurred in one-third of children and prevented further immune reconstitution, but had little impact on inflammatory biomarkers. Virological rebound to ≥5000 copies/ml was associated with arrested immune reconstitution, rising IL-6 and increased risk of clinical disease progression. Conclusions: As viral load testing becomes more available in sub-Saharan Africa, repeat testing algorithms will be required to identify those with virological rebound, who need switching to prevent disease progression, whilst preventing unnecessary second-line regimen initiation in the majority of children with detectable viraemia who remain at low risk of disease progression. Abstract : Supplemental Digital Content is available in the text